2015
DOI: 10.17219/acem/29760
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adjuvant Interferon Therapy on Hepatitis B/C Virus-Related Hepatocellular Carcinoma After Curative Therapy - Meta-Analysis

et al.

Abstract: Background. Hepatocellular carcinoma is the fifth most common malignant cancer in the world. Liver resection and local ablation are the most effective therapeutic approaches for most HCC patients. Recurrence after curative therapy is very common. Some studies reveal that IFNs have an effect on recurrence. While the opinion is disagreement. Objectives. The aim of this meta-analysis was to evaluate whether interferon therapy could reduce the recurrence of patients of hepatitis B/C virus-related hepatocellular ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…[ 12 , 13 ] IFN therapy has been confirmed to improve the survival rate of hepatitis-related HCC, but its effects on preventing recurrence seem conflicting. [ 16 19 ] Peg-IFN with an extended serum half-life and enhanced clinical efficacy has been adopted for the treatment of hepatitis-related HCC after curative therapy. However, studies on adjuvant Peg-IFN-based therapy for hepatitis-related HCC remain limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 12 , 13 ] IFN therapy has been confirmed to improve the survival rate of hepatitis-related HCC, but its effects on preventing recurrence seem conflicting. [ 16 19 ] Peg-IFN with an extended serum half-life and enhanced clinical efficacy has been adopted for the treatment of hepatitis-related HCC after curative therapy. However, studies on adjuvant Peg-IFN-based therapy for hepatitis-related HCC remain limited.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 , 15 ] Among them, interferon therapy was reported to be effective on reducing the mortality rate of hepatitis-related HCC after curative treatment, but its effect on reducing recurrence rates seems insignificant. [ 16 19 ]…”
Section: Introductionmentioning
confidence: 99%
“…Presenting at a younger age, or a different tumor biology may explain why viral patients had a similar prognosis to their non-viral counterparts. A recent meta-analysis showed that adjuvant interferon therapy after curative treatment for viral-associated HCC improved survival and decreased the recurrence rate [19]. This is in contrast to patients with NBNC-HCC who receive no therapeutic agents targeting the underlying cause of liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is the most common type of liver cancer and third prevalent cause of cancer-related death worldwide (Lodato et al, 2006;Tsuchiya et al, 2015;Wong & Frenette, 2011). Risk factors for HCC include hepatitis B or C infection, chronic liver disease, perpetual alcohol consumption, cirrhosis, and inherited metabolic diseases (Streba, Vere, Rogoveanu, & Streba, 2015;Tachi et al, 2018;Xu, Zhou, Wang, & Qiao, 2014;Xu, Li, Chen, & Liu, 2015). Early diagnosis and management of HCC should be secured for good prognosis and for increasing overall survival period (Tsuchiya et al, 2015;Wong & Frenette, 2011).…”
Section: Introductionmentioning
confidence: 99%